Analisa Faktor-faktor yang mempengaruhi Pemanfaatan Posyandu Lansia di Masa Pendemi Covid-19 di Desa Wonoagung Kabupaten Malang - Dedi Saifulah; Mohamad As`ad Efendy; Ridha Rachmathiany; Dwi Pudji Rahaju (Journal of Health Science Community, 2022)
The posyandu service for the elderly basically aims to maintain and provide preventive health services for the elderly. Activities carried out at the Posyandu for the elderly include checking daily activities including basic activities in life, mental status examination, hemoglobin examination, vitamin administration, nutritional status examination, diabetes mellitus examination, blood pressure measurement and health education. The purpose of this study was to analyze the effect of attitudes and knowledge on the utilization of the Bima Elderly Posyandu in Wonokitri Hamlet, Wonoagung Village, Tirtoyudo District, Malang Regency. This research approach is quantitative research. The research has two variables, namely the attitude and knowledge variables and the utilization variable for the Bima Elderly Posyandu in Wonokitri Hamlet, Wonoagung Village, Tirtoyudo District, Malang Regency. The population in this study were the elderly who visited the Posyandu for the elderly from January to February 2021 at the Bima Posyandu, as many as 82 elderly people, using the sampling method, namely the total sampling technique and the data analysis technique using multiple linear regression analysis. The results showed that there was an influence of attitude and knowledge on the utilization of the Bima Elderly Posyandu in Wonokitri Hamlet, Wonoagung Village, Tirtoyudo District, Malang Regency. The attitudes and knowledge of the elderly are expected to be directed more precisely so that they can increase the utilization of the Bima Elderly Posyandu in Wonokitri Hamlet, Wonoagung Village, Tirtoyudo District, Malang Regency.